Mortality and renal prognosis in isolated metformin-associated lactic acidosis treated with continuous renal replacement therapy and citrate-calcium-anticoagulation - Uusalo P; Järvisalo MJ (WILEY, 2022)
Introduction Use of metformin increases plasma lactate concentration and may lead to metformin-associated lactic acidosis (MALA). Previous studies have suggested severe MALA to have a mortality of 17%-21%, but have included patients with other coincident conditions such as sepsis. The treatment of choice is continuous renal replacement therapy (CRRT), which has been performed using heparin analogues or no anticoagulation in former studies. Materials and Methods Patients admitted to the Intensive Care Unit of Turku University Hospital Finland with lactic acidosis without any other recognizable etiology than concomitant metformin treatment who required CRRT between years 2010 and 2019 were included. CRRT was performed using regional citrate-calcium-anticoagulation. Data extracted included patient demographics, comorbidities, and clinical parameters at 6-hour intervals about 72 hours from admission. Creatinine and estimated glomerular filtration rate (eGFR) were measured at 1 year after MALA. Results A total of 23 patients with isolated MALA were included in the study. Median (IQR) pH was 6.88 (6.81-7.07) and lactate 16.1 (11.9-23.0) mmol/L on admission. Median (IQR) duration of CRRT was 62 (41-70) hours. Seven patients (30%) required mechanical ventilation with a mean duration of 6.0 +/- 3.0 days. 90-day mortality was 4.3% and 1-year mortality 13.0%. Creatinine (P = .02) and eGFR (P = .03) remained significantly altered at 1 year of follow-up compared to baseline. Conclusions MALA can be treated effectively and safely with CRRT and citrate-calcium-anticoagulation, usually required for 2-3 days. Mortality of patients with MALA treated with CRRT is low when other conditions inducing lactic acidosis are excluded. MALA episode may be associated with long-lasting kidney injury.